PENGEMBANGAN PUSTAKAWAN DI DINAS ARSIP DAN PERPUSTAKAAN KABUPATEN SUMEDANG - Fepi Febianti; Arip Rahman Sudrajat; Dedi Irawan (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2023)
This study aims to obtain objective data on how librarian development, obstacles in librarian development, and efforts to overcome librarian development obstacles at the Sumedang Regency Regional Archives and Library Office. The method used is a descriptive qualitative research method. The sampling technique used is Purposive Sampling with research informants as many as 5 (five) people. Data collection techniques through primary data collection techniques such as observation and interviews, secondary data collection techniques such as literature studies and documentation. In analyzing the data used Hasibuan model with steps: Data reduction, data presentation, Conclution drawing/ferification, and Triangulation. Based on the results of the study, it was concluded that librarian Development at the Regional Archives and Library Office of Sumedang Regency is still not optimal, because the benchmark development methods in the aspects of quality and quantity of librarian work are still low, the level of librarian discipline is still lacking, the effectiveness and efficiency of librarian work is still lacking, and the target has not been met.